The cGAS-STING Pathway in Hematopoiesis and Its Physiopathological Significance - Liao, Weinian; Du, Changhong; Wang, Junping (Frontiers in Immunology, 2020)
Cytosolic DNA sensing is a fundamental mechanism by which organisms handle various stresses, including infection and genotoxicity. The hematopoietic system is sensitive to stresses, and hematopoietic changes are often rapid and the first response to stresses. Based on the transcriptome database, cytosolic DNA sensing pathways are widely expressed in the hematopoietic system, and components of these pathways may be expressed at even higher levels in hematopoietic stem and progenitor cells (HSPCs) than in their certain progeny immune cells. Recent studies have described a previously unrecognized role for cytosolic DNA sensing pathways in the regulation of hematopoiesis under both homeostatic and stress conditions. In particular, the recently discovered cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) pathway is a critical modulator of hematopoiesis. Perturbation of the cGAS-STING pathway in HSPCs may be involved in the pathogenesis of hematopoietic disorders, autoimmune diseases and inflammation-related diseases and may be candidate therapeutic targets. In this review, we focus on the recent findings of the cGAS-STING pathway in the regulation of hematopoiesis, and its physiopathological significance including its implications in diseases and therapeutic potential.